2018
DOI: 10.1002/jper.17-0597
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different surgical approaches to increase peri‐implant mucosal thickness: A randomized controlled clinical trial

Abstract: ADM produces similar outcomes to sCTG in terms of mucosal augmentation at the time of implant placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 50 publications
(102 citation statements)
references
References 21 publications
1
96
0
Order By: Relevance
“…After screening titles and abstracts, 32 articles were selected for full‐text evaluation. Twenty‐six articles were further excluded from the qualitative and quantitative analyses; the reasons for exclusion are listed in Table . After full‐text review, no literature regarding tooth‐supported prostheses was identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening titles and abstracts, 32 articles were selected for full‐text evaluation. Twenty‐six articles were further excluded from the qualitative and quantitative analyses; the reasons for exclusion are listed in Table . After full‐text review, no literature regarding tooth‐supported prostheses was identified.…”
Section: Resultsmentioning
confidence: 99%
“…Aguirre-Zorzano et al 2013 25 Ahmed et al 2018 26 Akcali et al 2017 27 An et al 2009 28 Bhat et al 2015 31 Cosyn et al 2011 34 Cosyn et al 2013 33 Kan et al 2003 38 Kan et al 2011 37 Kim et al 2016 39 Nisapakultorn et al 2010 40 Paniz et al 2016 41 Patil et al 2013 42 Ross et al 2014 43 Spinato et al 2012 46 Studer et al 2000 47 Tao et al 2014 48 Yilmaz and Tözüm 2012 49 No control group Anderson et al 2014 29 Batista et al 2001 30 De Bruyckere et al 2015 35 Hutton et al 2018 9 Schneider et al 2011 44 Speroni et al 2010 45 Inadequate data to be analyzed Bianchi and Sanfilippo 2004 32 Jyothi et al 2013 36 favoring the SCTG group. There was a low (I 2 = 31%) heterogeneity among compared studies.…”
Section: Reason For Exclusion Author (Year)mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,13 Currently, the ADM is more routinely used for root coverage procedures (Fig. 2), [14][15][16][17][18][19] particularly when avoiding a second surgical site and minimizing patient morbidity is the primary concern. 2), [14][15][16][17][18][19] particularly when avoiding a second surgical site and minimizing patient morbidity is the primary concern.…”
Section: Decellularized Human Dermismentioning
confidence: 99%
“…1) and soft tissue augmentation at tooth or implant sites (Fig. 2), [14][15][16][17][18][19] particularly when avoiding a second surgical site and minimizing patient morbidity is the primary concern. 17,20,21 Although ADM is considered to be the graft substitute with the most similar outcomes to the connective tissue graft (CTG), 22 a recent network metaanalysis evaluating the changes in root coverage outcomes over time showed that only CTG-treated sites had a trend towards the stability of the gingival margin among the other root coverage techniques.…”
Section: Decellularized Human Dermismentioning
confidence: 99%